PENGARUH PEMANFAATAN ALAT EVALUASI ZEP QUIZ TERHADAP HASIL BELAJAR PAI SISWA KELAS XI SAINS - Alya Rushafah; Santi Lisnawati; Salati Asmahasanah (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aimed to determine the effect of using Zep Quiz as an evaluation tool on students’ learning outcomes in Islamic Religious Education (PAI). The research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The population consisted of all eleventh-grade science students at SMA Negeri 3 Kota Bogor, with a sample of 68 students divided into an experimental class and a control class. The research instruments included pretest and posttest multiple-choice tests and documentation. Data were analyzed using the Wilcoxon and Mann-Whitney tests with the assistance of SPSS 26. The findings showed that the experimental class experienced a significant increase in posttest scores after using Zep Quiz, while the control class showed no significant improvement. The statistical test results indicated a significance value of 0.000 < 0.05, meaning that Zep Quiz had a significant effect on students’ PAI learning outcomes.